ABOUT SOME NUMERICAL SEMIGROUPS WITH EMBEDDING DIMENSION THREE - Çelik, Ahmet; Alakuş, M.Sait; İlhan, Sedat (Al-Qadisiyah Journal of Pure Science, 2022)
we will examine a family of numerical semigroups embedding dimension three, such that S_u=< 8,8u+2,8u+9> where u >=1, u is integer . Also, we will give some relations between these semigroups and their Arf closure.